P-040 Sleep Disturbance and Fatigue in Adolescents and Young Adults with Crohn's disease: Characterization and Comparison to Healthy Controls. (March 2016) - Szigethy, Eva; Hashash, Jana; Vachon, Ashley; Mcauliff, Katheryn; Strassburger, Meredith; Rode, Noelle; Keljo, David; Fabio, Anthony; Regueiro, Miguel; Binion, David; Germain, Anne; Lotrich, Francis
Abstract : Background: Sleep disturbance and fatigue are common in patients with IBD. Sleep disturbance has recently been linked to inflammation and may be a risk factor for Crohn's disease (CD) relapse. Sleep is particularly critical during early adulthood; little is known about sleep disturbance in young IBD cohorts. This study evaluated sleep disturbance in adolescents and young adults with CD compared to healthy matched controls. Methods: Over 18 months, we screened all CD subjects ages 15 to 30 using the Pittsburgh Sleep Quality Index (PSQI) and Multidimensional Fatigue Inventory (MFI) at pediatric or adult GI clinic appointments. Participants scoring ≥7 on PSQI and ≥45 on MFI completed a further assessment, which included further probes of sleep using subjective (questionnaires) and objective (actigraphy) measures, a structured psychiatric interview for DSM-IV (SCID) for psychiatric diagnoses, anxiety and depression severity (Hamilton Rating Scale; HRSA and HRSD), CD activity (Harvey Bradshaw [HB]), and demographic information. Further details about IBD course, and medications were obtained by blinded investigators (J.G.H. and A.V.). Labs were drawn to assess inflammatory markers. Healthy controls in the same age range were screened for mental and physical conditions. Subjects with CD were compared to healthy controls using independent t -test for continuous variables and chi square (Fisher exact test) for categorical variables. Correlation analyses were used to further characterize clinical attributes of sleep disturbance and fatigue in both groups. Results: Over 18 months, 224 CD subjects were approached, 193 were screened, 93 screened positive on the PSQI and MFI with 51 completing the more comprehensive assessment. An additional 21 subjects met PSQI but not MFI criteria CD subjects were predominantly Caucasian, 63% female, with mean age of 23.5. Thirty healthy controls were assessed and matched on these variables. In the CD cohort, mean CD activity was mild, 24% were depressed, 57% had an anxiety disorder; 8% had post-traumatic stress disorder, and 2% had substance abuse (marijuana). Of the total CD sample, 42% met PSQI criteria for sleep disturbance and fatigue and 59% for sleep disturbance alone. Compared to healthy controls, the CD group had significantly greater sleep disturbance (PSQI 3.2 versus 10.8), fatigue (MFI 33.2 versus 64.6) and significantly greater anxiety and depression severity. The PSQI significantly correlated with MFI (r = 0.29) and HB (r = 0.24) in the CD group and MFI (r = 0.4) in the control group. The MFI significantly correlated HB (r = 0.48), PSQI (r = 0.29), HRSD (r = 0.38; minus sleep item), HRSA (r = 0.23; minus sleep item), and gender (r = 0.22, with females > males) in the CD group and PSQI (r = 0.4) HRSA (r = 0.39; minus sleep item), HRSD (r = 0.37; minus sleep item), and age (r = 0.28) in the control group. Conclusions: Adolescents and young adults with CD have higher rates of sleep disturbance and fatigue than normal controls. In the CD cohort, sleep disturbance and fatigue are significantly associated with higher CD activity with fatigue also being associated with depression and anxiety and being female. Future studies need to address if sleep interventions can improve fatigue, disease activity and psychiatric morbidity in young patients with IBD.